Linnaeus’ Orchids - Cribb, Phillip (Rheedea, 2007)
Linnaeus’ work on orchids can be traced back to the year 1737 in the first edition of his Genera Plantarum. His first work devoted to orchids was published in 1740 and formed the basis for his account in Species Plantarum published in 1753, in which he gave each species a binomial name. Given the overwhelming number of orchids, he included surprisingly few in Species Plantarum. This reflected the European origin of modern botany and the concentration of extra-European exploration on other matters such as conquest, gold, and useful plants. Nevertheless, the scope of Linnaeus’ work is broad, including plants from as far afield as India, Japan, China and the Philippines to the East and eastern Canada, the West Indies and northern South America to the west. Linnaeus captured the first flowering of plant exploration in this book, an occupation that he did much to stimulate through his adventurous students such as Afzelius, Forsskal, Thunberg and Persoon.